Integrasi Persepsi Kegunaan, Kualitas Sistem, dan Kredibilitas Algoritma dalam Mendorong Adopsi AI Marketing - Andhi Febisatria; Aryan Agus Pratama; Leonardo Davidsi Sipayung; Eureka Try Zarazwanty R. Laega; Zulfahmi (Universitas Negeri Padang, 2025)
Provide The utilization of Artificial Intelligence (AI) in digital marketing has grown rapidly, yet adoption levels among business actors remain varied. This study aims to analyze the influence of perceived usefulness, system quality, and algorithm credibility on the intention to use AI marketing. The research sample consisted of 100 business actors who have experience using AI marketing, distributed across Indonesia. A quantitative approach was employed, with data collected through surveys and analyzed using simple and multiple regression to examine the effects of independent variables on the intention to use AI marketing. The results indicate that perceived usefulness, system quality, and algorithm credibility have both partial and simultaneous positive and significant effects on the intention to adopt AI marketing. These findings highlight the importance of enhancing understanding of technological benefits, system reliability, and algorithm transparency to promote AI adoption in digital marketing practices, providing strategic implications for AI developers and business actors.